Tin suresinin tefsiri ve sure ışığında kutsal zaman ve mekan mefhumu - Polat, Emanullah (My University, 2001)
TEZ ÖZETİ Tezimiz Tîn Sûresinin Tefsîri ve Sûre Işığında Kutsal Zaman ve Mekân Mefhûmu ismini taşımakta olup Giriş, III Bölüm ve Sonuç olmak üzere toplam beş bölümden oluşmaktadır. Giriş Bölümünde, sûre tefsîrine duyulan ihtiyacın üzerinde durduktan sonra, konulu tefsîrin ehemmiyetini anlattık. Daha sonra da daha önce yapılmış Tîn Sûresi Tefsîrleri hakkında ve tezimizin sistemi hakkında bilgi verdik. I. Bölümde sûreyi daha çok klasik usullerle tefsîr etmeye çalışıp bu metodu, sûrenin nüzûl sebebi ve yeri, sûredeki ğarîb lafızlar, kıraat ihtilafları, sûrenin i'râbı, icmâlî tefsîri, fazileti ve sûreden çıkabilecek hükümler şeklinde uyguladık. II. Bölümde sûre ışığında kutsal mefhûmu ve kutsal zaman ve mekânlar üzerinde durduk. İşe kutsalın tarifi ile başlayıp sonra kutsalın kaynakları, İslâm öncesi dinler ve İslâm'da kutsallık anlayışını araştırıp her iki anlayışı karşılaştırdıktan sonra tartıştırdık. Daha sonra da eşya, zaman ve mekânın kutsallıklarını ve dinlerdeki mantığını araştırdık. III. Bölümde İslâm'ın kutsal olarak benimsediği bazı zaman ve mekânlar hakkında âyet ve hadîsleri derleyip değerlendirdikten sonra kutsalın psikolojik yönü üzerinde bazı fikirler sunduk. Sonuç Bölümünde ise Kutsalın hakikati ile yanlış temâyüller sonucu oluşan kutsallarla İslâm'ın mücâdelesini anlattık.

The thesis is titled as Tîn Sûresinin Tefsîri ve Sûre Işığında Kutsal Zaman ve Mekân Mefhûmu (The Exegesis of Surah Tin and the Concept of Holy Time and Plase in Light of the Surah). It is composed of an introduction, a conclusion, and there body chapters in between. The introduction part focuses on the exigency of Surah exegesis, thematic exegesis, the previous interpretations on Surah Tin, and the methodology of the thesis. In Chapter I, the Surah is elucidated and interpreted by classical methods. Accordingly, thesc methods are implemented taking into account the cause and place of revelation of the Surah, the ğarîb lexicons in the Surah, the articulation conflicts, the i'râb of the Surah, the abridged tafsir (exegesis), the virtue of the Surah, and religious laws derivable from the Surah. In Chapter II, in the light of the Surah, the concepts of holy and holy time and place are emphatically examined, Primarily, the definition of holy is given, and then the sources of holiness, the pre-Islamic and Islamic understandings of sacredness are investigated and discussed comparatively. In addition, the holiness of matter, time, and plase and their status in religions is put under projektors. In Chapter III, some Koranic verses and Hadiths (sayings of Mohammed (S.A.S.)) about some plases and times that Islam has adopted as sacred are assessed and interpreted. Later, the psychological dimensions of holiness are observed and commented on. Finally, in the conclusion part, the truth of holiness is put forth, and the struggle of Islam with untruthful glorifications and hallowings is analyzed and discussed.
Keywords: Ayetler ve sureler (Tefsir)